AGRIPRENEURIAL INTENTIONS AMONG BUSINESS STUDENTS: THE ROLE OF TEACHERS’ ENTREPRENEURIAL LEADERSHIP, CREATIVITY, AND SELF-EFFICACY - Nagi, Kelhoukhrietuo; Bordoloi, Dhrubajyoti; Ramalingam, Perumalraja; Ramasamy, Mani; Kath, Haithonlo (Bangladesh Journal of Multidisciplinary Scientific Research, 2025)
Agripreneurship has received increased attention in recent years as a solution to youth unemployment and rural development, particularly in regions like Nagaland, where agriculture plays a significant role in the economy.  Despite the incorporation of entrepreneurship education in the academic curriculum, its influence on the students remains unclear. This study examines the effect of Teachers' Entrepreneurial Leadership, along with Students' Creativity and Self-Efficacy, on agripreneurial Intention among business studies students in Nagaland. The study employed a simple random sampling method to collect primary data using structured questionnaires from 250 students enrolled in BBA and MBA programs from the five institutions offering business studies courses in Nagaland. Statistical tools, such as Cronbach's alpha reliability test, Correlation, and Regression analysis, were employed to analyze the collected data.  The study findings indicate a positive and significant correlation between Agripreneurial Intention and Teachers’ Entrepreneurial Leadership (r = 0.338), Creativity (r = 0.368), and Self-efficacy (r = 0.376), with p-values < 0.01. Regression analysis showed that the model explained 21.4% of the variance in Agripreneurial Intention (R² = 0.214), with a statistically significant value model (F = 22.365, p < 0.01). Self-efficacy emerged as the strongest contributor (β = 0.419), followed by Teachers’ Entrepreneurial Leadership (β = 0.372) and Creativity (β = 0.247). The study concludes that although business students in Nagaland generally exhibit a positive intention towards agripreneurship, not all the relevant factors influencing agripreneurial Intention were captured.JEL Classification Codes: Q0, Q130, Q190.